Peran Kepala Madrasah dalam Penguatan School Branding: Studi Kasus MIN 12 Nagan Raya - Dinda Safira; Herman; Ade Kurniawan (Media Manajemen Pendidikan, 2026)
This study explores the role of the madrasah principal in strengthening school branding at MIN 12 Nagan Raya through strategic programs aimed at improving educational quality. Using a qualitative descriptive approach, data were collected via observation, interviews, and documentation involving the principal, teachers, and parents. Findings reveal that the principal plays a crucial role in four areas: managing information media, enhancing teacher competencies, strengthening students’ remedial literacy, and fostering extracurricular activities. Although the madrasah lacks an official social media account, information management through the website is effectively handled by public relations staff under the principal’s guidance. Teacher competency development positively impacts learning quality, while student skill programs and extracurricular activities enhance achievements and build a positive institutional image. Strengthening branding is achieved through concrete initiatives that elevate overall educational standards. Theoretically, the study emphasizes that branding extends beyond promotional strategies to encompass comprehensive educational programs. Practically, the principal’s leadership integrates institutional development efforts, supported by collaboration among teachers, students, and parents. The findings highlight that effective leadership is a key factor in cultivating a strong, competitive institutional image and ensuring sustainable reputation and community trust.